Content-qualified antenatal care coverage in Lesotho: An ordinal logistic regression analysis of the 2023–2024 demographic and health survey - Kindu Yinges Wondie; Nuhamin Tesfa Tsega; Tazeb Alemu Anteneh; Alemneh Tadesse Kassie; Berihun Agegn Mengistie; Endalk Birrie Wondifraw; Getie Mihret Aragaw (PLoS ONE, 2026)
Background Despite high antenatal care contact coverage in Lesotho, the content and quality of care remains suboptimal. This study assessed the level and determinants of content-qualified antenatal care coverage using the 2023–2024 Lesotho Demographic and Health Survey. Methods Data were analyzed from 1,112 women aged 15–49 who had a live birth or stillbirth in the 2 years preceding the survey. Content-qualified antenatal care was constructed as a composite score (0–16) incorporating the timing of initiation, number of contacts, attendance of skilled providers, and receipt of 10 key content components. The score was categorized into ordered tertiles (low: 0–12, moderate: 13, high: 14–16). Survey-weighted ordinal logistic regression was used to identify factors associated with receiving higher content-qualified antenatal care. Results Overall, 28.1% of women had low, 32.4% moderate, and 39.5% high content-qualified antenatal care scores. Higher coverage was significantly associated with being married or living with a partner (AOR = 1.78, 95% CI: 1.12–2.83), having secondary (AOR = 2.05, 95% CI: 1.34–3.14) and higher education (AOR = 1.90, 95% CI: 1.21–2.98), using the internet at least once per week (AOR = 1.61, 95% CI: 1.08–2.40), wanted pregnancy (AOR = 2.87, 95% CI: 1.65–5.01), a smaller household (AOR = 1.36, 95% CI: 1.05–1.76), and higher community education (AOR = 1.38, 95% CI: 1.09–1.75). Conclusion Although antenatal care contact coverage is high in Lesotho, content-qualified coverage remains low and inequitable. Targeted interventions to improve maternal and community education, internet access, and pregnancy planning are essential to close the quality-coverage gap.